Sensorimotor dysfunction after limb fracture – An exploratory study. (21st March 2016) - Hall, J.; Llewellyn, A.; Palmer, S.; Rowett‐Harris, J.; Atkins, R.M.; McCabe, C.S.
Abstract: Background: Chronic pain is often associated with sensorimotor dysfunction but little is known about the early impact of limb fracture on sensory and motor performance. This exploratory study sought to assess these changes in patients with recent wrist and ankle fractures. A secondary aim was to determine the incidence of Complex Regional Pain Syndrome (CRPS) and its clinical features. Methods: Fifty‐three patients at a UK fracture centre underwent Quantitative Sensory Testing (QST), Motor Imagery (MI) and Body Perception Disturbance (BPD) assessments ≤5 weeks post‐fracture (Time 1). Subjective evaluation of recovery and clinical examination for CRPS was conducted 5 weeks later (Time 2, 50 patients). Patient‐reported outcomes of pain, psychological distress and limb function were collected at Times 1 and 2, and 6 months after T1 (Time 3, 36 patients, postal questionnaire). Results: Quantitative sensory testing at Time 1 demonstrated cold and pressure‐pain hyperalgesia in the fractured limb compared to the non‐fractured side ( p  <   0.05). Imagined movements were reported as significantly more difficult to perform on the fractured side ( p  <   0.001). There was evidence of BPD in the fractured limb, similar to that found in CRPS. The incidence of CRPS was 9.4%; however, individual signs and symptoms of the condition were commonly present (70% reported ≥ one symptom). Only 33% of patients reported to being 'back to normal' 6 months after fracture with 34% reporting ongoing pain. Conclusions: Limb fracture is associated with changes in pain perceptions, motor planning, and disruption to body perception. Signs and symptoms of CRPS, ongoing pain and delayed recovery post‐fracture are common. What does this study add?: In the immediate post‐fracture period: Body perception disturbance is reported in the fractured limb. Imagined movements of the fractured limb are less vivid and associated with pain This study contributes to the incidence literature on CRPS.